Pelatihan Pembuatan Logo Produk guna Mengoptimalkan Peluang Bisnis pada Remaja RT 02 RW 13 Kelurahan Rangkapan Jaya Lama Kota Depok - Sri Mulyani; Roni Fadli; Anggada Bayu Seta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The program partners are teenagers from RT 002 Rw 013, Rangkapan Jaya Lama Village, Depok City. The main problem for our partners is that hospitals still have the human resources to prepare them as well as possible for the challenges of the time. Design is the design of a product or object to be manufactured, and graphics is the science of forming dots and lines to provide information and form images related to the printing process. This graphic design training can be taught from the high school level, so soft-skills are relevant to creating product logos. With these soft-skills, teens can even turn it into a source of income by offering photo editing services. Additionally, this skill will enable students to easily edit photos in an ever-evolving technology environment. The hope is to kickstart entrepreneurship by launching graphic design services to support future steps in building the creative economy. Allowing you to start early to improve your skills and mindset to build.